Avaliação do uso do curto-circuito controlado (CCC) na soldagem de passes de enchimento pelo processo MIG/MAG duplo arame - Caimacan, Dumitru (2014)
The Double Wire MIG/MAG welding process (DW MIG/MAG) was developed to increase the production capacity of the conventional MIG/MAG welding process (single wire). The MIG/MAG DW generally uses pulsed current in both wires and a very short arc. However, the application of this technique is still not fully explored, particularly in relation to the potential improvements from the use of other metal transfer modes. One of the possible transfer modes is the Controlled Short-Circuit, which presents as main characteristic working with short arc, what has been a demand of DW MIG/MAG parameter settings. Furthermore, filling passes in automated welding would be an important application for the DW MIG/MAG. Thus, the objective of this work was to evaluate the use of the Controlled Short-Circuiting (CSC) operational mode infilling pass welding with the DW MIG/MAG process. The assessment was carried out through a comparative study between the conventional version of the process and a proposal applying pulsed current in the leader wire and CSC in the trailing wire (P-CSC). This comparison was established in welding of filling passes (single or multiple passes) on carbon steel plates in the flat and overhead positions. For comparative purposes, the average current at each wire, the volume of deposited metal per weld unit length, the type and size of the joint groove, the shielding gas chemical composition and the CTWD were kept constant. As assessment criteria, the surface finish and the geometry of the weld beads, the deposition rate and efficiency and the travel speed limits were used. The results show that the use of CSC in the trailing wire has low influence on the production capacity and on the operational maps of the DW MIG/MAG process, yet presents less spatter generation, better visual aspect of the welds and smaller volume of HAZ and molten zone. On the other hand, in the overhead position CSC did not maintain the same performance, presenting a more restrict operational map. In general, it was concluded that the use of CSC in the trailing wire presents advantages in comparison to the conventional DW MIG/MAG, in which pulsed current is used in both wires, for filling pass welding, mainly in the flat position.